Teaching Myself To See - Mukhopadhyay, Tito (punctum books, 2021)
Teaching Myself to See deals with Tito's struggles to participate in a world full of visual details. As a person with autism, Tito is visually selective, processing the myriad of details seeping in through the eye rather than the whole. Tracing Tito's experiences to learn to see in his own, "hyper-visual" way, through art, through magazines, through everyday life, Teaching Myself to See is a work of auto-anthropology, capturing in words, sentences, paragraphs, poems, a way of seeing that might seem so bewildering that doctors and psychologists told his mother he wouldn't be able to think. This book proves otherwise. By teaching us to look through his eyes, Tito shows us the miracle and immense complexity of sight, of neuro-atypicals and neuro-typicals alike.